2016
DOI: 10.1007/s10509-016-2758-4
|View full text |Cite
|
Sign up to set email alerts
|

Dust ion acoustic solitary structures in presence of nonthermal electrons and isothermal positrons

Abstract: The Sagdeev potential technique has been employed to study the dust ion acoustic solitary waves and double layers in an unmagnetized collisionless dusty plasma consisting of negatively charged static dust grains, adiabatic warm ions, and isothermally distributed electrons and positrons. A

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 86 publications
0
34
0
Order By: Relevance
“…Since then, theoretical studies have predicted supersolitons in a wide range of plasmas. These structures have been reported on both ion-acoustic (Ghosh & Sekar Iyengar 2014; Olivier, Maharaj & Bharuthram 2015; Singh & Lakhina 2015; Dutta & Sahu 2016; Paul & Bandyopadhyay 2016; Varghese & Ghosh 2016) and dust-acoustic (Hellberg et al. 2013; Verheest 2014) time scales.…”
Section: Introductionmentioning
confidence: 67%
“…Since then, theoretical studies have predicted supersolitons in a wide range of plasmas. These structures have been reported on both ion-acoustic (Ghosh & Sekar Iyengar 2014; Olivier, Maharaj & Bharuthram 2015; Singh & Lakhina 2015; Dutta & Sahu 2016; Paul & Bandyopadhyay 2016; Varghese & Ghosh 2016) and dust-acoustic (Hellberg et al. 2013; Verheest 2014) time scales.…”
Section: Introductionmentioning
confidence: 67%
“…we have considered Φ=φ (1) 1 for simplicity, and in Eq. ( 19), P is the dispersion coefficient which can be written as…”
Section: Derivation Of the Nlsementioning
confidence: 99%
“…The existence of massive dust grains in different electronpositron-ion (EPI) plasmas (viz., Jupiter's magnetosphere [1], Milky Way [2], auroral zone [3], accretion disks near neutron stars [2], the hot spots on dust rings in the galactic centre [3,4,5,6], interstellar medium [2], and around pulsars [5], etc.) does not only change the dynamics of the plasma medium but also significantly modifies the basic properties of electrostatic dust-acoustic (DA) waves (DAWs) [5,6,7] and dust-ionacoustic (DIA) waves (DIAWs) [1,2,3]. Esfandyari-Kalejahi et al [7] studied large amplitude DA solitary waves in EPI plasma, and demonstrated that the amplitude of the DA solitary waves increases with the charge state of dust grains.…”
Section: Introductionmentioning
confidence: 99%
“…Banerjee and Maitra [12] considered four components EPIDPM and studied electrostatic potential structures in presence of the massive dust grains and light positrons and observed that the hight of the potential structures increases with increasing value of massive dust number density but decreases with increasing light positron number density. Paul and Bandyopadhyay [13] demonstrated DI-AWs in an EPIDPM and highlighted the existence of both polarities solitary waves as well as positive and negative potential double layers but only positive super-solitons in an EPIDPM having positrons.…”
Section: Introductionmentioning
confidence: 99%
“…The electron-positron-ion-dust (EPID) plasma is a fully ionized gas comprises of electrons and positrons of equal masses but opposite polarity as well as ions and massive dust grains [1,2,3,4]. The simultaneous co-existence of the light positrons and heavy dust grains as well as electrons and ions in contrast to the usual plasma containing of electrons and ions in space and laboratory EPID plasma medium (EPIDPM) has rigourously changed the basic features of the propagation of nonlinear electrostatic waves, viz., Dust-acoustic (DA) waves (DAWs) [3,4,5,6], DA solitary waves (DA-SWs) [3,4], DA shock waves (DA-SHWs) [7], DA rogue waves (DA-RWs) [8,9,10,11], dust-ion-acoustic waves (DI-AWs) [12,13] in an EPIDPM, and has received much attraction to solve the profound mystery, and has identified in space plasmas, viz., active galactic nuclei [3,4], pulsar magnetospheres [3,4], interstellar clouds [3,4], supernova environments [3,4], early universe [12], the inner regions of the accretion disks surrounding the black hole as well as in laboratory experiments of cluster explosions by intense laser beams [14].…”
Section: Introductionmentioning
confidence: 99%